The dispersal of protoplanetary discs – III. Influence of stellar mass on disc photoevaporation. Issue 3 (9th October 2021) - Picogna, Giovanni; Ercolano, Barbara; Espaillat, Catherine C
ABSTRACT: The strong X-ray irradiation from young solar-type stars may play a crucial role in the thermodynamics and chemistry of circumstellar discs, driving their evolution in the last stages of disc dispersal as well as shaping the atmospheres of newborn planets. In this paper, we study the influence of stellar mass on circumstellar disc mass-loss rates due to X-ray irradiation, extending our previous study of the mass-loss rate's dependence on the X-ray luminosity and spectrum hardness. We focus on stars with masses between 0.1 and 1 M⊙, which are the main target of current and future missions to find potentially habitable planets. We find a linear relationship between the mass-loss rates and the stellar masses when changing the X-ray luminosity accordingly with the stellar mass. This linear increase is observed also when the X-ray luminosity is kept fixed because of the lower disc aspect ratio which allows the X-ray irradiation to reach larger radii. We provide new analytical relations for the mass-loss rates and profiles of photoevaporative winds as a function of the stellar mass that can be used in disc and planet population synthesis models. Our photoevaporative models correctly predict the observed trend of inner-disc lifetime as a function of stellar mass with an increased steepness for stars smaller than 0.3 M⊙, indicating that X-ray photoevaporation is a good candidate to explain the observed disc dispersal process.